Employing Concurrent Engineering technology in Product Design : An Exploratory Research of the Opinions of a Sample of workers in the men’s ready-made garments factory / Najaf Al. AShraf - Mohammed Abdulkadhim, Ali; Fahad Abid Ali, Mahmood; Jasim Mohammed, AbdulHussein (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to identify the philosophy of concurrent engineering and its foundations, as well as the philosophy of product design in the company under study, and for that the dimensions of Concurrent engineering were adopted: parallelism, standardization, integration, and optimization as an independent variable, and the dimensions of Product design: performance, reliability, conformity, durability, serviceability, aesthetics, perceived quality, special features, and this research was tested in the manufacturing sector by selecting a sample of the company’s employees, and among the most important conclusions, the company must develop a concept for Concurrent engineering technology and product design among its work priorities by adopting work strategies for the purpose of exploiting the marketing opportunities available in the markets, as for the most important recommendations Attempting to implement Concurrent engineering technology and product design in organizations in order to achieve progress and prosperity and keep pace with developments and changes in the laboratory.